Infant feeding and the media: the relationship between Parents' Magazine content and breastfeeding, 1972-2000 - Southwell Brian G; Foss Katherine A (BMC, 2006)
Abstract Mass media content likely influences the decision of women to breastfeed their newborn children. Relatively few studies have empirically assessed such a hypothesis to date, however. Most work has tended to focus either on specific interventions or on broad general commentary about the role of media. In this study, we examined infant feeding advertisements in 87 issues of Parents' Magazine, a popular parenting magazine, from the years 1971 through 1999. We then used content analysis results to predict subsequent changes in levels of breastfeeding among U.S. women. When the frequency of hand feeding advertisements increased, the percentage change in breastfeeding rates reported the next year generally tended to decrease. These results underscore the need to acknowledge the potential role of popular media content in understanding breastfeeding patterns and public health trends.